Personal Branding Pustakawan Di Perpustakaan - Rina Handayani (IAIN Ponorogo, 2015)
Using technology people introduce themselves into a brand, a community could accept them without any complicated process. Librarians as supporting the development of libraries in an institution that requires a personal branding good on him, it is to change the public image of a librarian. Using theoretical approach this study dealts with a response to Personal branding of Librarian. This study argues that the presence of the Personal branding will defnitely have a big impact on the Library. A library that has a good image in the world will certainly be able to develop the programs to increase the support of its librarian Personal branding. So that the realization of Personal branding, this institution will supports a good image.